Identification and expression of iron regulators in human synovium: evidence for upregulation in haemophilic arthropathy compared to rheumatoid arthritis, osteoarthritis, and healthy controls. (18th June 2013) - Nieuwenhuizen, L.; Schutgens, R. E.G.; van, B. S.; Wenting, M. J.; van, K.; Roosendaal, G.; Biesma, D. H.; Lafeber, F. P.J.G.
Summary Recurrent joint bleeding is the most common manifestation of severe haemophilia resulting in haemophilic arthropathy (HA). Iron plays a central role in the pathogenesis of the two main features of HA: synovitis and cartilage destruction. The aim of this study was to investigate the synovial presence of the iron regulator proteins ferroportin (FPN), hepcidin, haemoglobin scavenger receptor CD163 (CD163), feline leukaemia virus subgroup C (FLVCR), and heme carrier protein 1 (HCP‐1). A comparison of the expression in HA with rheumatoid arthritis (RA), osteoarthritis (OA), and healthy controls (HC) is made. Synovial expression of iron regulators was investigated by immunohistochemistry in human synovial tissue and in a murine haemophilia model. We demonstrate for the first time the synovial presence of the investigated iron regulator proteins. Expression of the iron regulator proteins FPN, CD163, FLVCR, and HCP‐1 was enhanced in HA in comparison to RA, OA, and HC synovium. In addition, in a murine haemophilia model of acute joint bleeding, synovial expression of FPN, CD163, and HCP‐1 was increased. In both human and murine experiment, synovial expression of hepcidin was not altered. These findings indicate the presence of iron regulator proteins in the synovium, demonstrate an enhanced expression of FPN, CD163, FLVCR, and HCP‐1 in HA, and suggest a synovial adaptation mechanism to maintain synovial iron homeostasis in HA.